CREATIVE TEACHING MODEL: AN ALTERNATIVE SOLUTION TO TEACHERS' PROBLEM IN PREPARING LESSON PLANS - Jonner Simarmata (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
One of the crucial and classical problems faced by English teachers in Indonesia is lesson planning. For several past decades. many models of teaching have been introduced. Even, in line with the implemention of K'13, a teaching model is also introduced to English teachers. However, based on my observations, out of the many teaching models, none has been satisfactory to teachers. Usually. teachers' confusion emmerges every time a new model is introduced. As a result, students' English learning outcomes are unsatisfatory as well. Through this paper, I would like to propose a simple model, which, in this paper, is called a Creative Teaching Model, which, I think, can be an alternative solution to teachers' problem in preparing a lesson. I believe that this model can bring about optimum teaching success due to the simplicity and effectiveness of this teaching model. For this, I have several reasons. First, this model applies simple procedure. Only within six steps, teachers can create not only effective teaching material but also effective teaching and learning strategies. Besides, this model accommodates all learning theories and language theories. Second, with this model, teachers can be as maximally creative as possible. Besides, PAIKEM principles can be incoorporated into this model. Hence, the learning outcomes are maximal as well. Third, every step in this model is easy, practical, and simple enough to formulate. So, in preparing a lesson plan, teachers do not need to spend much energy and time. Also, preparing a lesson is no longer a burden to teachers. Last but not least, this teaching model can be used for one or more sessions of class, depending on the situation and needs. The steps in the teaching model are as follows: l. formulating Learning Objective,2. selecting Motivating strategies, 3. selecting Presentation Strategies. 4. Developing Skill Practices, 5. Selecting Summing-up strategies, and 6. selecting Assessment. This teachi;rg model has been suocessfully implemented in one of the biggest language schools in Indonesia.